Preliminary evidence of effectiveness of preparations from Nigella sativa and its leading compound thymoquinone in periodontal therapy - Sigrun Chrubasik-Hausmann; Julia Vlachojannis; Marietta Wolf; Fabian Cieplik; Ali Al-Ahmad (Frontiers in Oral Health, 2026)
Background Preparations of Nigella sativa and its major bioactive compound thymoquinone (TQ) possess antioxidant, antimicrobial, anti-inflammatory, and wound-healing properties. These characteristics suggest potential utility as adjuncts in the management of gingivitis, mucositis, periodontitis, and peri-implantitis. Objective To critically evaluate the current clinical evidence regarding the use of Nigella sativa preparations and TQ in periodontal therapy. Methods A systematic literature search following PRISMA guidelines was conducted in PubMed, Embase, Scopus, Web of Science, and Cochrane CENTRAL for English-language clinical studies published through July 2026. Eligible studies investigated preparations of Nigella sativa or TQ for periodontal inflammatory diseases. Hand-searching was performed to identify additional relevant publications. Results Fourteen exploratory clinical trials were identified. Overall, adjunctive use of Nigella sativa preparations or TQ was associated with improvements in clinical periodontal outcome measures. However, interpretation is limited by small sample sizes, methodological heterogeneity, short follow-up periods, and insufficient characterization of the investigational products. Only one of the studies adequately reported the administered daily TQ dose. Discussion Without knowledge of the administered TQ dose, neither dose–response relationships nor reliable sample-size calculations for confirmatory trials can be established. Experimental evidence nevertheless supports the biological plausibility of the observed clinical findings and provides a rationale for further clinical investigation. Conclusions Current clinical evidence remains preliminary and hypothesis-generating despite encouraging findings. Future confirmatory randomized controlled trials should employ well-characterized, TQ-standardized preparations and report the administered TQ dose to enable reproducibility, dose–response assessment, and evidence-based study planning.